Progressive Genomic Instability in the Nup98-HoxD13 Model of MDS Correlates with Loss of the PIG-A Gene Product()() - Byrne, Michael (Neoplasia, 2014)
The Nup98-HoxD13 (NHD13) fusion gene was identified in a patient with therapy-related myelodysplastic syndrome (MDS). When transgenically expressed in hematopoietic cells, mice faithfully recapitulate human disease with serial progression from peripheral blood (PB) cytopenias and increased bone marrow (BM) blasts to acute leukemia. It is well accepted that genomic instability in dysplastic hematopoietic stem/progenitor cells (HSPC) drives the evolution of MDS to acute leukemia. Findings here demonstrate that reticulocytes, myeloid and lymphoid PB cells of NHD13 mice, display an increase in the age-associated loss of glycosylphosphatidylinositol-linked surface proteins versus wild type controls. These data correlate with a progressive increase in the DNA damage response as measured by γ-H2AX activity, accumulating BM blasts as the disease progresses and finally development of acute leukemia. These findings clearly demonstrate a state of progressive genomic instability that increases the likelihood of a “second hit” or complimentary mutation later in the disease to trigger development of acute leukemia and underscores the mechanistic nature of how the NUP98-HoxD13 transgene induces progression of MDS to acute leukemia. Additionally, these data support the use of the PIG-A assay as an efficient, real-time surrogate marker of the genomic instability that occurs in the MDS HSPCs. Key Point The PIG-A assay is a sensitive, nonlethal method for the serial assessment of genomic instability in mouse models of MDS.